PARTIAL CONTROL IS TRICKIER THAN WE THOUGHT - Snarska, Anna (Versita Ltd., de Gruyter, 2008)
This paper discusses partial control, a notoriously intricate phenomenon. Brought to the linguistic limelight only recently (cf. Landau 2000), its bizarre nature renders it a real challenge to any the- ory of control. I contribute to the Agree vs. Move debate on control by making an empirical claim concerning cases of what I call Parasitic Partial Control Effects which are extremely problematic to Landau’s Agree Theory of Control. To account for these facts, I propose a solution framed within the theory of control based on Move. Refining insights in Rodrigues (2007), I suggest that the licensing of the PC effect depends on the presence of the projection of wollP dominated by TP in the structure of the infinitive and the sideward movement of the DP controller from within the adjunct to the matrix. Thus, Landau’s claim that partial control is licensed only in complements must be loosened (if not dropped).
Keywords: PRO; control; sideward movement; pro